An assessment of the information needs and information-seeking behaviour of Members of Parliament (MPs) in Bangladesh. Issue 1 (9th January 2017) - Hossain, Md Uzzal; Hossain, Md Arman; Islam, Md Shariful
Abstract : Purpose: The purpose of this paper is to assess the information needs and information-seeking behaviour of Members of Parliament (MPs) in Bangladesh. It aimed at determining the information sources, preferred information format, frequency of seeking information and access to information and communication technology and online information services by the MPs. The study also intended to assess the role of parliament library for satisfying the information needs of the MPs. Design/methodology/approach: A survey method was adopted for data collection; the respondents were interviewed by the researchers with the guidance of a structured questionnaire. The questionnaire was read out for the respondents and filled up by the interviewers based on the answers they received. Fifty MPs were selected for the study using simple random sampling. The data were analysed with the help of weighted mean. Findings: The study found that the MPs mainly seek information to make a parliamentary request/inquiry, to make a speech and to make a decision. The most important sources of information were minutes of sessions, mass media, personal letters and information networks; and they preferred printed formats rather than online documents. The result also showed that only a few MPs were aware of the information services provided by the parliament library and were satisfied with the services they received. Originality/value: There has been no study carried out on the information needs and information-seeking behaviour of MPs in Bangladesh prior to this research. The study will help the policymakers to improve the library services for MPs in Bangladesh.